Associations Between Dietary Inflammatory Index and Sex Hormones Among 6- to 19-Year-Old Children and Adolescents in NHANES 2015–2016 - Ma, Yuxia; Li, Ruiqiang; Zhan, Wenqiang; Huang, Xin; Zhou, Yutian; Sun, Yan; Tian, Hao; Zhu, Huichen; Yin, Bowen (Frontiers in Endocrinology, 2022)
Objectives: This study aimed to assess the relationship between dietary inflammatory index (DII) and sex steroids in children (6-11 years old) and adolescents (12-19 years old) in the U.S. National Health and Nutrition Examination Survey, 2015–2016. Methods: Participants between the ages of 6-19 have 24-hour dietary intake data, serum sex hormones [total testosterone (TT), estradiol (E2)], and sex hormone-binding globulin (SHBG) available data ( n = 1382). The free androgen index (FAI) is calculated as TT divided by SHBG and the ratio of TT to E2 (TT/E2). The constructed puberty state is defined as high levels of steroid hormones (TT≥50 ng/dL in men, E2≥20 pg/ml in women) or onset of menarche. Multiple linear regression analysis was stratified by gender-age and gender-pubertal status groups to evaluate the association between DII and sex hormone levels. Results: After adjusting for covariates, the association between consecutive DII and sex hormone indicators by gender and age group. In male adolescents, DII is always negatively correlated with TT (P-trend = 0.09), FAI (P-trend = 0.03) and E2 (P-trend = 0.01), and monotonically positively correlated with SHBG (P-trend = 0.02).In female adolescents, with the increase of DII, a significant positive correlation with SHBG was observed (β 0.017, 95%CI: 0.009,0.053) (Table 3). Among female adolescents, a significant negative correlation between DII and TT and a significant positive correlation between SHBG were observed in this group. Moreover, DII is positively correlated with SHBG of prepubertal males and negatively correlated with FAI of prepubertal females. Conclusions: Pro-inflammatory diets are associated with decreased levels of certain sex steroid hormones (TT, FAI, and E2) and increased levels of SHBG in adolescents or adolescents. These associations show a certain degree of the gender-dependent pattern. However, there is little evidence that there is a significant association in children or prepubertal children. Further research needs to be carried out to verify our results.